INTERNALISASI NILAI-NILAI KARAKTER DAN KEPRIBADIAN MAHASISWA PENDIDIKAN AGAMA ISLAM MELALUI PENDEKATAN HUMANIS-RELIGIUS (EDUKASIA, 2017)
CHARACTER VALUES AND PERSONALITY INTERNALISATION OF ISLAMIC EDUCATION STUDENTS THROUGH HUMANIST-RELIGIOUS APPROACH. Islamic Teacher Training and Education Faculty has a strategic role in the effort to counteract demoralization and dehumanization. One of the efforts is by maximizing the academic process. The purpose of this study is to discover how the implementation of character education through a religious humanist approach is. Sources of data were from leaders, lecturers of Personality Development Subject, student and related matters. To get the data more deeply, researcher used Snowball Technique. Techniques used for collecting data were multiple methods. They were interview, documentation and observation. The results show that the character education design is hiddencurriculum. In the process done through the activities of Tridarma Perguruan Tinggi. It can be implemented through emphasizing regulations of lectures and socialization. They are building harmonious, humanist and religious relationships, kinship, promoting compassion, positive habituation, building a positive mindset of students, meaningful learning, lecturers as the living model, and integration of Islamic values. The easy access to the source of religious values will be able to maximize the effort to have cadres of future teachers who have humanist and religious character and personality.